Serum Lipid Profile Status in Prediabetes and Newly Diagnosed Type 2 Diabetes Mellitus Patients in a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medical Biochemistry, 2025)
Dyslipidemia in diabetic patients plays an important role in acceleration of macrovascular atherosclerosis. Considering the prevalence and increased risk of cardiovascular diseases in diabetic patients, it is becoming necessary to assess the lipid profile of both prediabetic and diabetic individuals. Serum lipid profile including the levels of total cholesterol, triglyceride, HDL-cholesterol and LDL-cholesterol of prediabetics and newly diagnosed type 2 diabetes mellius (T2DM) patients have been studied in this study. Hyperlipidemia has documented causative relation with CAD, but the major risk associated with diabetes may be due to the associated hyperlipidemia. The study revealed that dyslipidemia is present in both prediabetes and newly diagnosed type 2 diabetics. Decreased serum high-density lipoprotein cholesterol (HDL-C) levels was found in prediabetes whereas it was normal in T2DM. Thus, the study clearly shows the relationship between prediabetics and type 2 diabetes with dyslipidemia, which may influence increased coronary artery disease (CAD) risk.Bangladesh J Med Biochem 2020; 13(1): 01-04